Development and Implementation of Clinical Practice Guidelines: An Update and Synthesis of the Literature With a Focus in Application to Spinal Conditions. Issue 1 (May 2019) - Tetreault, Lindsay; Nater, Anick; Garwood, Philip; Badhiwala, Jetan H.; Wilson, Jefferson R.; Fehlings, Michael G.
Study Design: Review. Objectives: The objectives of this review are to ( a ) summarize the role of clinical practice guidelines (CPGs), ( b ) outline the methodology involved in formulating CPGs, ( c ) provide an illustration of these principles using a CPG developed for degenerative cervical myelopathy, and ( d ) highlight the importance of knowledge translation. Methods: A review of the literature was conducted to summarize current standards in CPG development and implementation. Results: CPGs are systematically developed statements intended to affect decisions made by health care providers, policy makers, and patients. The main objectives of CPGs are to synthesize and translate evidence into recommendations, optimize patient outcomes, standardize care, and facilitate shared decision making among physicians, patients, and their caregivers. The main steps involved in the development of CPGs include defining the clinical problem, assembling a multidisciplinary guideline development group and systematic review team, conducting a systematic review of the literature, translating the evidence to recommendations, critically appraising the CPG and updating the document when new studies arise. The final step in developing a CPG is to implement it into clinical practice; this step requires an assessment of the barriers to implementation and the formulation of effective dissemination strategies. Conclusion: CPGs are an important component in the teaching and practice of medicine and are available for a wide spectrum of diseases. CPGs, however, can only be used to influence clinical practice if the recommendations are informed by a systematic review of the literature and developed using rigorous methodology. The opportunity to transform clinical management of spinal conditions is an attractive outcome of the application of high-quality CPGs.